Investigation of anterior knee pain after total hip replacement: a pilot study - Robertson, Claire; Coutts, Fiona; Bell, Jonathan (Physiotherapy research international : the journal for researchers and clinicians in physical therapy, 2007)
Background and Purpose. There is no previous research to determine if total hip replacement can lead to anterior knee pain. The idea for the present study came from clinical observation of anterior knee pain (AKP) after total hip replacement, and the objective was to investigate anterior knee pain after total hip replacement. Method. The study used a prospective single‐system design with a convenience sample. Six men and seven women were assessed before and at six weeks after total hip replacement for the presence and degree of AKP, using a step‐down test combined with a visual analogue scale (VAS). Measurements were also taken of leg length, hip and knee motion, thigh circumference and hamstring length using previously validated tests. Results. Eight of thirteen subjects had AKP at six weeks post‐operation. Active knee flexion was reduced post‐operation (p < 0.0007), and proximal, mid‐ and distal thigh circumferences were increased (p < 0.0001). Eleven of 13 subjects demonstrated leg lengthening (p < 0.0001), and 10/11 subjects demonstrated a reduction in passive knee flexion (p < 0.002). All biomechanical data were correlated against the VAS. Although none were statistically significant, both decreased active and passive knee flexion, and increased thigh circumference exhibited the greatest trend with the VAS. Conclusions. The results of the present study cannot be compared to other studies, as there are no previous studies on AKP after total hip replacement. Current outcome measures for total hip replacement do not measure for AKP, although it may potentially hinder full functional recovery. Orthopaedic surgeons and physiotherapists need to be aware if this is a possible complication of total hip replacement, and hence further research is required to test external validity. Copyright © 2006 John Wiley & Sons, Ltd.